Interaction Of Environmental And Dietary Factors In The Pathogenesis Of Cardiovascular Diseases - Farida Azizova (International Journal of Medical Sciences And Clinical Research, 2025)
The article examines the relationship and interaction between environmental and dietary factors in the pathogenesis of cardiovascular diseases (CVD). Based on an analysis of current scientific sources, it emphasizes that environmental pollution (PM2.5, NO₂, heavy metals, organic toxins) and unhealthy dietary patterns (excess trans fats, salt, and antioxidant deficiency) exert a synergistic effect on the development of inflammatory and degenerative changes in the cardiovascular system. Particular attention is given to the mechanisms of interaction between these factors, which include oxidative stress, endothelial dysfunction, and mitochondrial disturbances. The article substantiates the need for a comprehensive preventive approach based on improving diet quality and reducing exposure to environmental risks.